Sustainable manufacturing for rubber waste industries with integrated circular economy - Arzo Rani; Sakshi Tyagi; Anshika Singh; Abhinav Goel; Shubham Kumar Singh; Anand Chauhan (Discover Sustainability)
Abstract Introduction The rubber industry generates significant waste during production, particularly from defective and excess materials such as scrap from production processes. Incorporating recycling and refurbishing processes within the framework of a circular economy can significantly reduce environmental impact and enhance resource efficiency. Objective of the study Addressing the above-discussed issues, the study adopts the principles of circular economy to develop a mathematical model for optimizing the recycling and refurbishing processes in the rubber industry. The primary objective is to minimize costs, reduce waste, and mitigate environmental impact while incorporating economic factors such as inflation and carbon tax policies. Methodology The methodology involves formulating a zero-waste inventory model that integrates recycling, refurbishing, and sustainable production practices. The Hessian matrix is used to optimize the non-linear model, with numerical simulations and sensitivity analysis validates its effectiveness. Result The results indicate the utilization of recycled rubber as raw material, which can reduce waste disposal by 95% and significantly lower production costs. Sensitivity analysis highlights the impact of critical parameters, such as inflation and recycling costs, on the model’s performance. Conclusion and implication The study concludes that integrating carbon taxes and circular economy principles addresses economic and environmental challenges in the rubber industry. Industries can achieve cost stability by mitigating inflationary pressure and promoting recycled materials. The findings provide actionable insights for policymakers and industry stakeholders to implement sustainable manufacturing practices, low-carbon logistics, and recycling technology to ensure a resilient and sustainable industrial future.